Surface enhanced Raman spectroscopic investigation of orchil dyed wool from Roccella tinctoria and Lasallia pustulata. (4th August 2014) - Doherty, B.; Gabrieli, F.; Clementi, C.; Cardon, D.; Sgamellotti, A.; Brunetti, B.; Miliani, C.
<x xml:space="preserve">Abstract</x> In this work Raman spectroscopic techniques have been utilized to characterize the vibrational spectral features of orchil dyed wool samples. Specifically, it is noted by surface enhanced Raman spectroscopy that wool dyed purple with two historically used orchil species (Roccella tinctoria and Lasallia pustulata) show spectral differences possibly owing to their specific dye‐precursor constituents. The additional natural dyestuff woad (Isatis tinctoria L.) overdyeing the R. tinctoria orchil dyed wool is a further challenge when distinguishing the mixed dye components given by the co‐adsorption of the dyestuffs as permitted by the selection rules of surface enhanced Raman spectroscopy. Furthermore, the effects of dilution of the L. pustulata species in its spectral detection have been assessed along with the evaluation of subsequent lichen extract boiling before dyeing which resulted in the detection of a degraded form of the orchil dye. Proof of concept included the surface enhanced Raman spectroscopy (SERS) investigation of a purple dyed tapestry (XVI century) which permitted an aged orchil dye to be determined. This contribution utilizes SERS as a fast, reproducible and specific method for both orchil dye detection and alteration induced by degradation. Copyright © 2014 John Wiley & Sons, Ltd.